SISTEM ANTRIAN PADA PUSKESMAS SUKAMERINDU - Kalsum, Toibah Umi; Siswanto, Siswanto (UNIVED Press, 2012)
The growth of technology was progress so fast and show benefist that better than never to business world. One of all technologies is present computer as media witch so help us, this media can facilitate work of same one. This happen used by companies and afficials prossession of government or corporate to increasing their effectiveness and efficiency in work. As one of public service, Puskesmas Kampung Bali city has purpose to giving health service to society that want it.As one of public service in healthy area, Puskesmas Kampung Bali Bengkulu City in serving to patient who get difficulty at the first time when come to Puskesmas Kampung Bali. It is couse less information so patient don’t know where are they go to regist and what is form of service that will they recive later never the lass can handled, if must passing a queue that spend time to much and sometimes will produce a messiness. It is mean that often happen getting the start of each other, sometimes any patient who unresponsibility or not want to queue with good manner, but they get service earlier ( except UGD ). So the other patient feels unsatisfiedly about service in Puskesmas. This happen caused by any bad of sytem so decelerate information that needed by patient.In design og system of patient queue in Puskesmas Kampung Bali Bengkulu City by using visual basic 6.0 after that do analysis process of queue system that going on in Puskesmas of Bengkulu City with design interface or appearance of input and output that produced by this queue system. Than from produce of queue sytem after implementationed, tested, and finally writer can take conclusion that is = process of patient queue must do faster and accurate, so that service can be more maximal, mor effective cause queue system has integrated in one special program in system form. By this system, administrator enough operate the program if want to looking for information about way of using this progam only with look facility using program that consist in this program so not need administaror in a continue and also not spond time to much.